A new species of Arbomia Sato & Wang (Lepidoptera, Geometridae, Ennominae) from Guangxi, Southern China - Jiang, Nan; Xue, Dayong; Han, Hongxiang (Zootaxa, 2014)
The genus Arbomia was described as a monotypic genus by Sato & Wang, 2004, based on Arbomia kishidai Sato & Wang, 2004 from China (Guangdong) and Vietnam. Since then, no new species of Arbomia has been described. Recently we have examined all the specimens of Arbomia in IZCAS, including those collected during recent expeditions, and have found one new species. The purpose of this paper is to describe the new species A. trigonoprocessa sp. nov., to reported Arbomia kishidai for the first time from the provinces of Zhejiang, Hunan, Fujian, and Guangxi of China, and to provide diagnostic characters and illustrations of the external features and genitalia of the two Arbomia species.